Distal medial tibial locking plate for fixation of extraarticular distal humeral fractures; an alternative choice for fixation - Ali Cagdas Yorukoglu; Ahmet Fahir Demirkan; Nihal Buker (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to describe an alternative fixation method for distal humeral extra-articular fractures through posterior approach using distal tibia anatomic locking plate; and to evaluate the patient's functional outcome and union condition. Methods: Eighteen patients (11 men and 7 women; average age of 37.0 ± 17.3 years (range: 18–73 years)) with a distal humeral extra-articular fracture who were treated with distal tibial medial locking plate were included into the study. The mean follow up time was 36.2 ± 16.7 (12–57) months. Functional results were evaluated with perception of pain, range of joint motion, grasp and pinch strengths. Results: Union was achieved in 17 of 18 patients. Only one patient had non-union due to infection and underwent debridement. The mean time for union was 7.8 ± 5.9 months (2–20). Patient perception of pain was X = 1.88 ± 2.50 and X = 4.55 ± 2.68, respectively, at rest and activity. The active ranges of joint motion were adequate for functional use. General functional state of affected extremity (DASH-T) was perfect (X = 27.14 ± 25.66), the performance of elbow joint was good (X = 84.44 ± 11.57). There were no differences in the comparison of grasp and pinch grip of patients with uninvolved extremity (p > 0.05). Conclusions: In distal humeral extra-articular fractures, use of distal medial tibia plate has advantages such as providing high rates for union, low rates for complication, and early return to work with early rehabilitation, therefore it may be considered a fixation choice that can be used for distal humeral extra-articular fractures. Level of evidence: Level IV, therapeutic study. Keywords: Distal humeral fractures, Distal tibial locking plate, Fixation, Osteosynthesis, Extraarticular, Distal humerus